2020
DOI: 10.1167/tvst.9.11.29
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Sensitivity Testing in Retinal Vein Occlusion Using a Novel Stimulus

Abstract: Purpose This study evaluated a novel tool known as the motion diamond stimulus (MDS), which utilizes contrast-generated illusory motion in dynamic test regions to determine contrast sensitivity (CS). Methods Patients with treated unilateral retinal vein occlusions (RVOs) underwent three assessments: the MDS, the Pelli-Robson (PR), and the National Eye Institute's Visual Function Questionnaire (VFQ-25). The MDS assessment produced two data end points, α and β. The α valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…One of the effects of RVO is damage to visual function, including a significant decline in contrast sensitivity threshold (McIntosh et al, 2010; Mishra et al, 2020). Since we had previously found that EC Casp9 regulated retinal edema and retinal neuronal death in RVO (Avrutsky et al, 2020), we sought to explore whether EC Casp9 was implicated in damage to contrast sensitivity discrimination.…”
Section: Resultsmentioning
confidence: 99%
“…One of the effects of RVO is damage to visual function, including a significant decline in contrast sensitivity threshold (McIntosh et al, 2010; Mishra et al, 2020). Since we had previously found that EC Casp9 regulated retinal edema and retinal neuronal death in RVO (Avrutsky et al, 2020), we sought to explore whether EC Casp9 was implicated in damage to contrast sensitivity discrimination.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the MDS, a novel CS testing method in development, is discussed in detail in prior studies. 18 This is the first study to test the MDS assessment in patients with AMD. CS can be helpful in early detection, monitoring, and assessing treatment response in several ocular conditions.…”
Section: Discussionmentioning
confidence: 99%
“… 9 The utility and accuracy of the gold standard Pelli-Robson CS test has been challenged, 16 and limitations of the PR include static field testing, influence of lighting, reflection, and fading on the physical chart, learning effect on repeat testing, and the necessity for patients to recognize letters. 18 Alternate CS tests such as the MDS have been developed to account for the above-mentioned limitations. The MDS tests CS in a dynamic field, is a digital rather than physical tool, has randomized directions on repeat testing, and does not require letter recognition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations